Integrated Management Systems: Leading Strategies and Solutions - Pardy, Wayne; Andrews, Terri (Bernan Press, 2019)
Management system standards have been adopted by millions of organizations around the world. With such widespread use, comes many questions on not only the standards themselves,but how to use them, and for those considering multiple standards, how to maximize and leverage their common features. In Integrated Management Systems: Leading Strategies and Solutions, the authors use their wealth of knowledge and practical experience inHealth Safety, Environment and Quality Management System(HSEQ) Standards to profile how best to use and integrate these management system standards into your day to day operations and business models.